Battery negative electrode material and preparation method thereof
By using modified zinc oxide and mesoporous carbon in the negative electrode material of zinc nickel battery, the problems of zinc dendrites and corrosion are solved, and the cycle performance and life of the battery are improved.
Patent Information
- Application Number
- CN202411970103.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
AI Technical Summary
The zinc negative electrode material of zinc nickel batteries is prone to form zinc dendrites during use, corrosion and passivation, resulting in the separator being pierced, the battery being short-circuited, and the electrode being deformed, thereby reducing the cycling performance and life of the battery.
A battery negative electrode material is adopted, including zinc, modified zinc oxide, binder, ammonium tetramolybdate, sodium allyl sulfonate and water. The electrical properties of the negative electrode material are improved by surface modification of modified zinc oxide and the addition of mesoporous carbon.
Through the synergistic effect of modified zinc oxide and mesoporous carbon, the contact area between the negative electrode material and the electrolyte is improved, dendrite generation is suppressed, the stability of the material is enhanced, and the circulation performance and life of the battery are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery negative electrode material and a preparation method thereof. Background Art
[0002] With the change of people's concept of battery use and the continuous advancement of technology, alkaline batteries, especially those that do not contain mercury, are becoming more and more popular. At the same time, the requirements for battery performance of modern electrical products are also continuously improving. Zinc-nickel batteries, as an alkaline secondary battery, are mainly composed of zinc negative electrode, nickel positive electrode and potassium hydroxide electrolyte. The abundant reserves and wide distribution of zinc help reduce the production cost of batteries, and no harmful pollutants are generated during the production, use and disposal process. The discharged materials can also be recycled, which fully meets the requirements of environmental protection and sustainable development.
[0003] In addition, zinc-ion batteries have a long service life, which reduces the replacement frequency and maintenance costs of batteries, making them very suitable for scenarios such as base station energy storage in remote areas. However, zinc negative electrode materials currently face some problems during use, such as the formation of zinc dendrites, corrosion, and passivation, which may cause the diaphragm to be punctured, leading to battery short circuits, electrode deformation, and ultimately reducing the battery's cycle performance and life. Therefore, the research and development of battery negative electrode materials with excellent electrical properties plays a vital role in meeting people's growing demand for electricity. Summary of the invention
[0004] The present invention provides a battery negative electrode material and a preparation method thereof, which solves the problem of poor electrical performance of the battery negative electrode material in the related art.
[0005] The technical solution of the present invention is as follows: The present invention provides a battery negative electrode material, comprising the following components in parts by weight: 86-100 parts of zinc, 10-20 parts of zinc oxide, 5-8 parts of binder, 2-6 parts of ammonium tetramolybdate, 2-3 parts of sodium allyl sulfonate, 50 parts of water; The zinc oxide includes tetrapod-shaped zinc oxide whiskers and spherical zinc oxide; The weight ratio of the four-needle zinc oxide whisker to the spherical zinc oxide is 1:9-9:1.
[0006] As a further technical solution, the weight ratio of the four-needle zinc oxide whiskers to the spherical zinc oxide is 3-6:2.
[0007] When the weight ratio of tetrapod-shaped zinc oxide whiskers to spherical zinc oxide is 3-6:2, the electrical properties of the battery negative electrode material can be further improved.
[0008] As a further technical solution, the diameter of the four-needle zinc oxide whisker is 0.5-5 μm, and the length is 10-50 μm; the particle size of the spherical zinc oxide is 50-100 nm.
[0009] As a further technical solution, the zinc oxide is modified zinc oxide, the raw materials of the modified zinc oxide include zinc oxide and a modifier, and the modifier includes N-trimethylsilaneacetamide.
[0010] Surface modification of zinc oxide using N-trimethylsilaneacetamide can increase the active sites of zinc oxide, which is beneficial to the adsorption and reaction of zinc ions, thereby further improving the electrical properties of negative electrode battery materials.
[0011] As a further technical solution, the preparation method of the modified zinc oxide comprises the following steps: dispersing the N-trimethylsilane acetamide in dimethylformamide, adding the zinc oxide, stirring, and drying to obtain the modified zinc oxide.
[0012] As a further technical solution, the weight ratio of the zinc oxide to the N-trimethylsilaneacetamide is 40:2-5.
[0013] When the weight ratio of zinc oxide to N-trimethylsilaneacetamide is 40:2~5, the electrical properties of the negative electrode battery material can be further improved.
[0014] As a further technical solution, the modifier also includes mesoporous carbon.
[0015] The inventors found that when the modifier also includes mesoporous carbon, the electrical properties of the negative electrode battery material can be further improved by modifying zinc oxide with mesoporous carbon and N-trimethylsilane acetamide. The reason may be that the presence of mesoporous carbon can increase the specific surface area of the negative electrode material, and can also make zinc oxide and N-trimethylsilane acetamide work better, thereby further improving the modification effect of N-trimethylsilane acetamide on zinc oxide, so that the negative electrode material is better in contact with the electrolyte, thereby further improving the electrical properties of the negative electrode battery material.
[0016] As a further technical solution, the weight ratio of the N-trimethylsilaneacetamide to the mesoporous carbon is 1-4:1.
[0017] When the weight ratio of N-trimethylsilaneacetamide to mesoporous carbon is 1-4:1, the electrical properties of the negative electrode battery material can be further improved.
[0018] As a further technical solution, the pore diameter of the mesoporous carbon is 130~150nm.
[0019] As a further technical solution, the preparation method of the modified zinc oxide comprises the following steps: A1, mixing the zinc oxide and the mesoporous carbon, adding the mixture to a hydroxypropyl methylcellulose solution, drying, calcining, and crushing to obtain a mixture; A2, dispersing the N-trimethylsilane acetamide in dimethylformamide, adding the mixture, stirring, and drying to obtain the modified zinc oxide; The weight ratio of the zinc oxide to the hydroxypropyl methylcellulose solution is 1:1.2.
[0020] As a further technical solution, the mass fraction of the hydroxypropyl methylcellulose solution is 3% to 6%.
[0021] As a further technical solution, during the calcination, the temperature is 280-300° C. and the time is 1-2 hours.
[0022] As a further technical solution, the binder includes one or two of hydroxypropyl methylcellulose and polyvinyl alcohol.
[0023] The present invention also provides a method for preparing a negative electrode material for a battery, comprising the following steps: S1. Mix the remaining components except the binder, sodium allyl sulfonate and water to obtain a mixture; S2. After dissolving the sodium allyl sulfonate in water, add the mixture and the binder, mix well, and dry to obtain the battery negative electrode material.
[0024] The working principle and beneficial effects of the present invention are: In the present invention, the battery negative electrode material includes two kinds of zinc oxide, namely, four-needle zinc oxide whiskers and spherical zinc oxide. The four-needle zinc oxide whiskers and the spherical zinc oxide have a synergistic effect. By compounding the two different zinc oxides, the contact area between the negative electrode material and the electrolyte is increased, and the negative electrode material can form a staggered and dense barrier layer, thereby effectively inhibiting the formation of dendrites, so that the battery negative electrode material has good stability, thereby improving the electrical properties of the battery negative electrode material. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the following examples and comparative examples, the average diameter of the four-needle zinc oxide whisker is 3 μm and the length is 30 μm; the average particle size of the spherical zinc oxide is 80 nm; the pore size of the mesoporous carbon is 140 nm; and the viscosity of the hydroxypropyl methylcellulose is 100,000 mPa.s.
[0027] Example 1 A battery negative electrode material, comprising the following components in parts by weight: 86 parts of zinc, 10 parts of zinc oxide, 5 parts of hydroxypropyl methylcellulose, 2 parts of ammonium tetramolybdate, 2 parts of sodium allyl sulfonate, 50 parts of water; The zinc oxide comprises 1 part of tetrapod-shaped zinc oxide whiskers and 9 parts of spherical zinc oxide; The preparation method thereof comprises the following steps: S1. Evenly mix the remaining components except hydroxypropyl methylcellulose, sodium allyl sulfonate and water to obtain a mixture; S2. After dissolving sodium allyl sulfonate in water, add the above mixture and hydroxypropyl methylcellulose, mix well, and dry to obtain a negative electrode material for a battery.
[0028] Example 2 A battery negative electrode material, comprising the following components in parts by weight: 94 parts of zinc, 16 parts of zinc oxide, 6.5 parts of hydroxypropyl methylcellulose, 4 parts of ammonium tetramolybdate, 2.5 parts of sodium allyl sulfonate, 50 parts of water; The zinc oxide comprises 6 parts of tetrapod-shaped zinc oxide whiskers and 10 parts of spherical zinc oxide; The preparation method thereof comprises the following steps: S1. Evenly mix the remaining components except hydroxypropyl methylcellulose, sodium allyl sulfonate and water to obtain a mixture; S2. After dissolving sodium allyl sulfonate in water, add the above mixture and hydroxypropyl methylcellulose, mix well, and dry to obtain a negative electrode material for a battery.
[0029] Example 3 A battery negative electrode material, comprising the following components in parts by weight: 100 parts of zinc, 20 parts of zinc oxide, 8 parts of hydroxypropyl methylcellulose, 6 parts of ammonium tetramolybdate, 3 parts of sodium allyl sulfonate, 50 parts of water; The zinc oxide comprises 18 parts of tetrapod-shaped zinc oxide whiskers and 2 parts of spherical zinc oxide; The preparation method thereof comprises the following steps: S1. Evenly mix the remaining components except hydroxypropyl methylcellulose, sodium allyl sulfonate and water to obtain a mixture; S2. After dissolving sodium allyl sulfonate in water, add the above mixture and hydroxypropyl methylcellulose, mix well, and dry to obtain a negative electrode material for a battery.
[0030] Example 4 The only difference between this embodiment and embodiment 2 is that in this embodiment, the zinc oxide includes 14 parts of tetrapod-shaped zinc oxide whiskers and 2 parts of spherical zinc oxide.
[0031] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, the zinc oxide includes 9.6 parts of tetrapod-shaped zinc oxide whiskers and 6.4 parts of spherical zinc oxide.
[0032] Example 6 The only difference between this embodiment and embodiment 2 is that in this embodiment, the zinc oxide includes 12 parts of tetrapod-shaped zinc oxide whiskers and 4 parts of spherical zinc oxide.
[0033] Example 7 The only difference between this embodiment and embodiment 6 is that in this embodiment, the zinc oxide is modified zinc oxide, and its preparation method comprises the following steps: dispersing 1 part of N-trimethylsilane acetamide in 50 parts of dimethylformamide, adding 40 parts of zinc oxide (wherein the weight ratio of tetrapod-shaped zinc oxide whiskers to spherical zinc oxide is 3:1), stirring, and drying to obtain modified zinc oxide.
[0034] Example 8 The difference between this embodiment and embodiment 7 is that, in this embodiment, 6 parts of N-trimethylsilaneacetamide are added.
[0035] Example 9 The difference between this embodiment and embodiment 7 is that, in this embodiment, 2 parts of N-trimethylsilaneacetamide are added.
[0036] Example 10 The difference between this embodiment and embodiment 7 is that, in this embodiment, 5 parts of N-trimethylsilaneacetamide are added.
[0037] Embodiment 11 The only difference between this embodiment and embodiment 10 is that in this embodiment, the preparation method of modified zinc oxide includes the following steps: 40 parts of zinc oxide (wherein the weight ratio of tetrapod-shaped zinc oxide whiskers to spherical zinc oxide is 3:1) and 5 parts of mesoporous carbon are mixed and ground to obtain modified zinc oxide.
[0038] Example 12 The difference between this embodiment and embodiment 10 is that, in this embodiment, the preparation method of modified zinc oxide comprises the following steps: A1. Mix 40 parts of zinc oxide (wherein the weight ratio of tetrapod-shaped zinc oxide whiskers to spherical zinc oxide is 3:1) and 4 parts of mesoporous carbon, add into 48 parts of 4% hydroxypropyl methylcellulose solution, dry, calcine at 290° C. for 1.5 h, and grind to obtain a mixture; A2. Disperse 1 part of N-trimethylsilane acetamide in 50 parts of dimethylformamide, add the above mixture, stir, and dry to obtain modified zinc oxide.
[0039] Example 13 The only difference between this embodiment and embodiment 12 is that, in this embodiment, 4.5 parts of N-trimethylsilaneacetamide and 0.5 parts of mesoporous carbon are added.
[0040] Embodiment 14 The only difference between this embodiment and embodiment 12 is that, in this embodiment, 2.5 parts of N-trimethylsilaneacetamide and 2.5 parts of mesoporous carbon are added.
[0041] Embodiment 15 The only difference between this embodiment and embodiment 12 is that, in this embodiment, 4 parts of N-trimethylsilaneacetamide and 1 part of mesoporous carbon are added.
[0042] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, only 10 parts of tetrapod-shaped zinc oxide whiskers are added.
[0043] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, only 10 parts of spherical zinc oxide are added.
[0044] The battery negative electrode materials prepared in Examples 1 to 15 and Comparative Examples 1 to 2 were made into negative electrode sheets with a size of 10 cm×3 cm, and the positive electrode sheets were nickel positive electrode sheets with a size of 15 cm×10 cm. After the negative electrode sheets and the positive electrode sheets were placed in an electrolytic cell to assemble a zinc-nickel battery, the number of cycles and the capacity retention rate after 100 cycles were tested, wherein the electrolyte was a mixture of 25 wt % KOH and 1.5 wt % LiOH, and the zinc-nickel was charged and discharged in a constant current charge and discharge mode with a voltage range of 0 to 2.5 V. The test results are shown in Table 1 below.
[0045] Table 1 Electrical performance tests of Examples 1 to 15 and Comparative Examples 1 to 2
[0046] Compared with Comparative Examples 1 and 2, the number of cycles and the capacity retention rate after 100 cycles of Example 1 are significantly improved, indicating that when the battery negative electrode material includes two types of zinc oxide, namely, tetrapod-shaped zinc oxide whiskers and spherical zinc oxide, the tetrapod-shaped zinc oxide whiskers and spherical zinc oxide have a synergistic effect and can effectively improve the electrical properties of the battery negative electrode material.
[0047] Compared with Examples 2 and 4, the number of cycles and the capacity retention rate after 100 cycles of Examples 5-6 are improved, indicating that when the weight ratio of tetrapod-shaped zinc oxide whiskers to spherical zinc oxide is 3-6:2, the electrical properties of the battery negative electrode material can be further improved.
[0048] Compared with Example 6, the number of cycles and the capacity retention rate after 100 cycles of Examples 7 to 10 are improved, indicating that surface modification of zinc oxide using N-trimethylsilaneacetamide can further improve the electrical properties of the negative electrode battery material.
[0049] Compared with Examples 7 to 8, the number of cycles and the capacity retention rate after 100 cycles of Examples 9 to 10 are improved, indicating that when the weight ratio of zinc oxide to N-trimethylsilaneacetamide is 40:2 to 5, the electrical properties of the negative electrode battery material can be further improved.
[0050] Compared with Examples 10 to 11, the number of cycles and the capacity retention rate after 100 cycles of Examples 12 to 15 are improved, indicating that the electrical properties of the negative electrode battery material can be further improved by jointly modifying zinc oxide with mesoporous carbon and N-trimethylsilaneacetamide.
[0051] Compared with Examples 12 to 13, the number of cycles and the capacity retention rate after 100 cycles of Examples 14 to 15 are improved, indicating that when the weight ratio of N-trimethylsilaneacetamide to mesoporous carbon is 1 to 4:1, the electrical properties of the negative electrode battery material can be further improved.
[0052] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A battery negative electrode material, characterized in that: The composition comprises the following components in parts by weight: 86-100 parts of zinc, 10-20 parts of zinc oxide, 5-8 parts of binder, 2-6 parts of ammonium tetramolybdate, 2-3 parts of sodium allyl sulfonate, 50 parts of water; The zinc oxide includes tetrapod-shaped zinc oxide whiskers and spherical zinc oxide; The weight ratio of the four-needle zinc oxide whisker to the spherical zinc oxide is 1:9-9:
1.
2. A battery negative electrode material according to claim 1, characterized in that: The weight ratio of the four-needle zinc oxide whisker to the spherical zinc oxide is 3-6:
2.
3. A battery negative electrode material according to claim 1, characterized in that: The zinc oxide is modified zinc oxide, and the raw materials of the modified zinc oxide include zinc oxide and a modifier, and the modifier includes N-trimethylsilaneacetamide.
4. A battery negative electrode material according to claim 3, characterized in that: The preparation method of the modified zinc oxide comprises the following steps: dispersing the N-trimethylsilane acetamide in dimethylformamide, adding the zinc oxide, stirring, and drying to obtain the modified zinc oxide.
5. A battery negative electrode material according to claim 3, characterized in that: The weight ratio of the zinc oxide to the N-trimethylsilane acetamide is 40:2-5.
6. A battery negative electrode material according to claim 3, characterized in that: The modifier also includes mesoporous carbon.
7. A battery negative electrode material according to claim 6, characterized in that: The weight ratio of the N-trimethylsilaneacetamide to the mesoporous carbon is 1-4:
1.
8. A battery negative electrode material according to claim 6, characterized in that: The preparation method of the modified zinc oxide comprises the following steps: A1, mixing the zinc oxide and the mesoporous carbon, adding the mixture to a hydroxypropyl methylcellulose solution, drying, calcining, and crushing to obtain a mixture; A2, dispersing the N-trimethylsilane acetamide in dimethylformamide, adding the mixture, stirring, and drying to obtain the modified zinc oxide; The weight ratio of the zinc oxide to the hydroxypropyl methylcellulose solution is 1:1.
2.
9. A battery negative electrode material according to claim 1, characterized in that: The binder includes one or both of hydroxypropyl methylcellulose and polyvinyl alcohol.
10. The method for preparing a negative electrode material for a battery according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Mix the remaining components except the binder, sodium allyl sulfonate and water to obtain a mixture; S2. After dissolving the sodium allyl sulfonate in water, add the mixture and the binder, mix well, and dry to obtain the battery negative electrode material.